2004
DOI: 10.1111/j.1478-3231.2004.0933.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase 1 is partly compensating for nitric oxide synthase 3 deficiency in nitric oxide synthase 3 knock‐out mice and is elevated in murine and human cirrhosis

Abstract: Increased NOS-1 mRNA and protein levels and partially maintained in vitro NO-production in aortae of NOS-3 KO mice suggest that NOS-1 may partially compensate for NOS-3 deficiency. BDL-induced increase in aortic NOS-1 mRNA and protein levels hint that not only NOS-3, but also NOS-1 may be involved in the regulation of systemic hyperdynamic circulation and portal hypertension. Upregulation of NOS-1 mRNA levels in hepatic arteries of portal hypertensive patients suggests possible clinical significance for these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…Xu and colleagues (35) showed that 7-NI blocked the development of hyperdynamic circulation in cirrhotic rats. Furthermore, increased nNOS mRNA and/or protein levels have been documented in aortae of BDL mice (3), mesenteric arteries of portal hypertensive rats (10), and hepatic arteries of cirrhotic patients (3). Finally, a preeminent role of nNOS would explain the persistence of hyperdynamic circulation in portal hypertensive double-knockout mice lacking the genes for both eNOS and inducible NOS (8) and cirrhotic knockout mice lacking the eNOS gene (12).…”
Section: Discussionmentioning
confidence: 95%
“…Xu and colleagues (35) showed that 7-NI blocked the development of hyperdynamic circulation in cirrhotic rats. Furthermore, increased nNOS mRNA and/or protein levels have been documented in aortae of BDL mice (3), mesenteric arteries of portal hypertensive rats (10), and hepatic arteries of cirrhotic patients (3). Finally, a preeminent role of nNOS would explain the persistence of hyperdynamic circulation in portal hypertensive double-knockout mice lacking the genes for both eNOS and inducible NOS (8) and cirrhotic knockout mice lacking the eNOS gene (12).…”
Section: Discussionmentioning
confidence: 95%
“…It is well-known that NO is an important physiologic mediator of erectile function derived from nonadrenergic noncholinergic neurotransmission [52]. However, excess NO is involved in the pathogenesis of hepatic [53,54] and extrahepatic [55,56] manifestations of cirrhosis. In the current study, the penile NO was over-expressed in bile duct ligated rats.…”
Section: Discussionmentioning
confidence: 99%
“…This is phenomenon is well-established, for example, by several studies in other models showing that the deletion of eNOS results in increased expression of nNOS isoform [76][77][78][79]. It is less clear; however, whether this isoform compensation occurs in the case of iNOS deletion strategies.…”
Section: Limitationsmentioning
confidence: 80%